Fecal microbiota transplantation is safe and tolerable in patients with multiple sclerosis: A pilot randomized controlled trial - Al, Kait F.; Craven, Laura J; Gibbons, Shaeley; Parvathy, Seema Nair; Wing, Ana Christina; Graf, Chantelle; Parham, Kate A; Kerfoot, Steven M; Wilcox, Hannah; Burton, Jeremy P; Kremenchutzky, Marcelo; Morrow, Sarah A; et al. (Multiple sclerosis journal - experimental, translational and clinical, 2022)
Background Patients with MS have an altered gut microbiota compared to healthy individuals, as well as elevated small intestinal permeability, which may be contributing to the development and progression of the disease. Objective We sought to investigate if fecal microbiota transplantation was safe and tolerable in MS patients and if it could improve abnormal intestinal permeability. Methods Nine patients with MS were recruited and provided monthly FMTs for up to six months. The primary outcome investigated was change in peripheral blood cytokine concentrations. The secondary outcomes were gut microbiota composition, intestinal permeability, and safety (assessed with EDSS and MRI). Results The study was terminated early and was subsequently underpowered to assess whether peripheral blood cytokines were altered following FMTs. FMTs were safe in this group of patients. Two of five patients had elevated small intestinal permeability at baseline that improved to normal values following FMTs. Significant, donor-specific, beneficial alterations to the MS patient gut microbiota were observed following FMT. Conclusion FMT was safe and tolerable in this cohort of RRMS patients, may improve elevated small intestinal permeability, and has the potential to enrich for an MS-protective microbiota. Further studies with longer follow-up and larger sample sizes are required to determine if FMT is a suitable therapy for MS.